Pendeteksian Objek Hasil Pengepresan Kaleng dan Botol dengan Metode You Only Look Once (YOLO) yang Diaplikasikan pada Mesin Sortir Pembelajaran PBL - Diono, Diono; Wicaksono, M. Jaka Wimbang; Jefiza, Adlian; Prayudha, Dimas Rama (JURNAL INTEGRASI, 2024)
Image Processing is a technique of processing images with the input of an image and producing an image as well. One of the functions of Image Processing that the author wants to apply is the detection of an object from a still image or a moving image. In this application, the object to be identified by the author will be applied to the PBL sorting machine in the form of cans and bottles. In designing this system, the You Only Look Once (YOLO) method is used and several libraries. YOLO is an algorithm for detecting an object using an artificial neural network (ANN) from an image where this network divides the image into several regions and predicts each bounding box and probability for each region of the image. The author also uses a webcam to detect the object and a Servo Motor as a sorter on the PBL Sorting Machine. The result of this final project is that the system can detect objects cans and bottles properly and produce precise accuracy and is able to move the sorter based on the output data from the detection results.